New Signage Design: connecting people and spaces = Nouveau design de signalétique = Nuevo diseño de señalética = Novo design de sinalização - Shaoqiang, Wang; Teuler, Marie-Pierre; De Cos Pinto, Jesús; Carrillo, Élcio (Promopress, 2015)
This book collects the latest and freshest signage and wayfinding designs from all over the world. They are all tailor-made for specific spaces, including schools, hotels, shopping malls, libreries, parking garages and medical facilities.